An AI framework and a metamodel for collaborative situations: Application to crisis management contexts. (29th September 2020) - Benaben, Frederick; Fertier, Audrey; Montarnal, Aurélie; Mu, Wenxin; Jiang, Zheng; Truptil, Sebastien; Barthe‐Delanoë, Anne‐Marie; Lauras, Matthieu; Mace‐Ramete, Guillaume; Wang, Tiexin; Bidoux, Loïc; Lamothe, Jacques
Abstract: Identifying, designing, deploying and maintaining accurate collaborative networks of organizations (e.g. responders in a crisis situation) are key activities in nowadays ecosystems. However, there is a lack regarding formal approaches dedicated to characterize collaborative networks of organizations. Formal descriptions of collaborative situations, that could be used, transformed, computed and exploited would be of great benefit for the quality of such collaborative networks. This article presents a model‐based AI framework for describing collaborative situations and the associated formal metamodel dedicated to be instantiated to characterize collaborative situations in a very wide range of application domains. This metamodel (describing collaborative situation between organizations) is structured according to four complementary dimensions: the context (social, physical and geographical environment), the partners (the involved organizations, their capabilities resources and relations), the objectives (the aims of the network, the goals to be the achieved and the risks to avoid, etc.) and the behaviour (the collaborative processes to be implemented by the partners to achieve the objectives in the considered context ). Besides, this metamodel can be extended for some precise application domains. This article focuses on this mechanism in the specific context of crisis management.